Responding to contempt. Nietzsche and a genealogy of homosexual literature in Colombia - Hincapié-García, Alexánder (Íkala, Revista de Lenguaje y Cultura, 2018)
Homosexual literature in Colombia can be understood as an effort to respond to the habitual contempt with which homosexuals are represented. Contempt is a mimic of affections capable of linking different social forces directed against certain forms of life. The theoretical-methodological perspective adopted ap-proximates the genealogy proposed by Nietzsche. Therefore, genealogy is not the search of any origin, but it is the work of producing interpretations that interrupt the chain of socially accepted signs and meanings.